Potensi Ekstrak Sansevieria sp. dan Cymbopogon nardus sebagai Disinfektan Udara Alami - Redi Yudha Irianto; Sri Slamet Mulyati; Nurul Hidayah; Ine Srinati (Buletin Keslingmas, 2026)
Indoor environments should protect occupants from unwanted pollutants and hazards; however, indoor pollutant concentrations are often higher than those outdoors. Indoor bioaerosols pose a risk factor for clinical conditions such as asthma, irritation, allergies, and respiratory disorders. The growth of airborne pathogenic microbes can be inhibited using extracts of snake plant (Sansevieria sp.) and citronella grass (Cymbopogon nardus), which contain citronellal, nerol, phenolics, triterpenoids, alkaloids, and tannins as antibacterial compounds. This study aimed to determine the difference in mean total airborne microbial counts following the application of a single extract of 70% ethanol Sansevieria sp. 30% and a combined extract of 70% ethanol Sansevieria sp. 30% + Cymbopogon nardus 10% using a humidifier. A Posttest Only Control Group Design was employed in a 100 m³ miniature room using 81 petri dishes as air sampling media. The mean total microbial count for the single extract was 161.1 CFU/m³ (62 % reduction), while the combined extract yielded 54.2 CFU/m³ (88 % reduction). An Independent T-test revealed a significant difference between the single Sansevieria sp. extract and the combined Sansevieria sp. and Cymbopogon nardus extract (p-value < 0.001). The combined extract of Sansevieria sp. and Cymbopogon nardus was proven to be more effective in reducing total airborne microbial counts compared to the single extract.